Responses of Soil Microbial Communities Associated with Phosphorus Transformation to Land-Use Alternations in a Meadow Grassland, Northeast China - Li Yu; Ying Zhang; Zhenbo Cui; Chengyou Cao (Microorganisms)
Land-use changes in meadow grasslands in semi-arid areas usually significantly affect soil environment and microbiota. However, studies on the response of soil P-cycle-related microbial communities to land-use conversions are still limited. In this study, a series of land-use types including upland field, paddy field, poplar plantation, and their adjacent natural meadow grassland in the Horqin Sandy Land of Northeast China were selected, and the diversities and structures of soil microbial communities involved in organic P mineralization (phoD-harboring community) and inorganic phosphate solubilization (gcd-harboring community) were investigated by the high-throughput sequencing technique. Land-use type had significant influences on soil physicochemical properties, enzymatic activities, and P conversion rates, thereby altering the structures of soil gcd and phoD communities. Soil phoD microbes are more abundant and have more contributions to available P than gcd microbes. The responses of gcd or phoD communities to land-use type were characterized as the quantitative shift in the relative abundance of dominant taxa; however, the basic compositions of the two communities were slightly affected. Soil pH, EC, and nutrient contents (including organic matter and total and available N, P, and K) all significantly affected soil gcd and phoD microbial communities. The abundance of phoD and gcd genes varied with land-use type and could be used as indicators for estimating the bioavailability of soil P.